Effects for the incorporation of five-atom thioacetamido nucleic acid (TANA) backbone on hybridization thermodynamics and kinetics of DNA duplexes - Kaur, Harleen; Arora, Amit; Gogoi, K.; Solanke, P.; Gunjal, Anita D.; Kumar, Vaijayanti A.; Maiti, Souvik (Journal of Physical Chemistry B, 2009)
Thermodynamic studies of nucleic acids serve not only to widen our understanding on the nature and strength of forces that stabilize nucleic acids in a myriad of structural states they assume but also to facilitate the development of databases that could be used to predict the stability and selectivity of probe/primer-sets required in a broad range of nucleic acid-based diagnostic and therapeutic protocols. In the current study, we investigated the effect of a novel, backbone-modified ``thioacetamido linkage'' (TANA) on thermodynamics of hybridization, binding kinetics, and conformation of a DNA duplex. The modification comprises of an extended five-atom amide (N3'-CO-CH(2)-S-CH(2)) linker, as opposed to four-atom phosphodiester linker backbone present in DNA. One to three TANA-substitutions have been introduced in the linker backbone of two thymidine residues of one of the strand of the DNA duplex. Using spectroscopic and calorimetric techniques, we observed that TANA destabilizes the DNA helix by lowering the favorable enthalpy parameter of duplex formation. TANA center dot DNA duplexes were found to adopt a conformation toward an A-type duplex as shown by circular dichroism spectroscopy studies. Analysis of differential scanning calorimetry data indicated a nonzero heat capacity change, Delta C(p), accompanying the duplex formation. The average Delta C(p) change per duplex was found to be 832.5 cal mol(-1) K(-1), giving an average base-pair change of 59.5 cal (mol of base pairs)(-1) K(-1). Hybridization kinetic measurements using surface plasmon resonance indicated a decrease in binding affinity parameter (K(A)) that originates from higher dissociation rate constants (k(d)). Furthermore, optical melting studies showed that increasing the number of modifications results in a modest change in the number of counterions taken up during duplex formation.

Probing the furanose conformation in the 2 `-5 ` strand of isoDNA:RNA duplexes by freezing the nucleoside conformations - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2011)
Sugar conformations in the isoDNA strand of isoDNA : RNA duplexes are preferred S-type locked/frozen in contrast to N-type locked conformations preferred in DNA: RNA duplexes.

Detection and knockdown of MicroRNA-34a using thioacetamido nucleic acid - Soni, Kartik; Gupta, Shivani; Gokhale, Sachin S.; Dey, Rakesh; Gunjal, Anita D.; Kumar, Vaijayanti A.; Pillai, Beena (Nucleic Acid Therapeutics, 2013)
Thioacetamido nucleic acids (TANA) contain a backbone modification of dinucleotides consisting of a 5-atom amide linker N3'-COCH2-S-CH2 at thymidine or thymidine-cytidine dimer blocks. Here, the chemical synthesis of the TANA linked 5-methyl-cytidine-cytidine ((Me)cc) dimer block and its incorporation into the DNA sequence, complementary to human microRNA 34 (miR-34) is described. Further, for the first time, we demonstrate the biological applications of TANA modified oligonucleotides in detection and intracellular knockdown of a cancer related microRNA in comparison with DNA containing locked nucleic acid (LNA) and 2'-O-methyl modifications. The human microRNA miR-34 is a pro-apoptotic microRNA under the transcriptional control of protein 53 (p53). It gets expressed in response to DNA damage and regulates several cell cycle and apoptosis related targets. Here, we show that the TANA modified antisense oligonucleotide binds specifically to miR-34a, allowing its detection using primer extension. We also show that, using the TANA modified antisense oligonucleotide against miR-34a, intracellular levels of miR-34 can be reduced, and consequently, the expression of its target oncogene V-myc myelocytomatosis viral related oncogene, neuroblastoma derived (MYCN) is enhanced. Further, we assessed the toxicity and serum stability of the oligonucleotide to conclude that it is suitable for detection and modulation of the vital biomarker and tumor suppressor microRNA.

Synthesis and structural studies of S-type/N-type-locked/frozen nucleoside analogues and their incorporation in RNA-selective, nuclease resistant 2 `-5 ` linked oligonucleotides - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Gonnade, Rajesh G.; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2013)
2'-endo locked or frozen (S-type)/3'-endo locked or frozen (N-type) nucleoside analogues were synthesized. Conformational analysis based on (3)J(HH) and NOE measurements is presented which is further confirmed by X-ray crystal structural studies. 2'-5' isoDNA oligonucleotides (ON) were synthesized using these modified nucleoside analogues and UV-T-m studies of the resultant 2'-5' isoDNA : RNA duplexes reflect the site-and sequence-dependent effects and confirm that the S-type sugar conformations were preferred over the N-type sugar geometry in such duplexes.

Functional isoDNA aptamers: modified thrombin binding aptamers with a 2'-5'-linked sugarphosphate backbone (isoTBA) - Gunjal, Anita D.; Fernandes, Moneesha; Erande, Namrata D.; Rajamohanan, P. R.; Kumar, Vaijayanti A. (Chemical Communications, 2014)
The regioisomeric 3'-deoxy-2'-5'-linked thrombin binding DNA aptamers (isoTBAs) were chemically synthesized and their ability to form unimolecular anti-parallel G-quadruplexes in the presence of K+ ions was evaluated. These modified sequences retain the function of the native thrombin binding aptamer (TBA), exhibit better stability against exonuclease and are capable of slowing down the process of blood clotting.

Investigation of the effect of amino acid chirality in the internucleoside linker on DNA:DNA and DNA : RNA duplex stability - Seema Bagmare; Gunjal, Anita D.; Kumar, Vaijayanti A. (Tetrahedron, 2015)
Enzymatically and chemically stable amide-linked di/oligonucleosides are highly desired synthetic targets in which the phosphodiester linkages in native DNA are replaced by amide linkers of appropriate length and stereochemistry. The five-atom amide-linked dimers, synthesized from 3'-amino-3'-deoxy thymidine, (alpha-(L/D) proline/prochiral glycine and thymidine/uridine-4'carboxylic acid derivatives, were incorporated into the DNA backbone to achieve partial replacement of selected phosphodiester linkages. The results stressed the importance of the chirality of linker amino acid. D-Proline was found to be the most compatible as an internucleoside linker in the DNA backbone to stabilize the complexes with DNA or RNA as compared to L-proline and glycine. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amino acid; Chiral amide linkage; DNA; Five-atom amide linkage; L/D-Proline